Os límites entre galego e asturleonés en Asturias. - Frías Conde, Francisco Xavier (Revista de Filología Románica, 2001)
The linguistie border between Galicia» and Asturian in Asturias was t’irst sWdied by Ramón Menéndez Pidal in Ihe early lOth’s. He was the first scbolar who set Ihe fine between both languages o» tite right side of river Navia. After him other important Spanisb línguists confirmed titis first sight. José Menéndez García was rnuch more precise and took two capital features to establish the frontier: the diphthongisation or lack of diphtbongisation of botb short Latin ¡el and lo! vowels and tite dropping or conservation of intervocalie ¡nl. Dámaso Alonso recognised tite language spoken between tite rivers Lo and Navia as Galician, despite sorne Asturian features are easily recognised (on tite otiter sido Galician features can be found in tite wetern Asturian dialect) Finally Diego Catalán added sorne new elements, including morpitological ones, tbat permitted to set a mucit more precise frontier (liowever Menendez’s studies are probably tite most accurate np to now). Our contribution to titís series of studies is a large list of phonological, morpitological and sytactical elements titar are different in both languages, though sorne (lalician elements are to be found in westem Asturian and vice versa sorne Asturian elernents are to be found in easrem Galician,